Pengaruh Sales Promotion dan Kualitas Informasi pada Media Sosial Instagram terhadap Minat Berkunjung Wisatawan di Karanganjar Koffieplantage - Dian Afifudin; Indra Tjahaja Amir; Dita Atasa (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this research is to analyze the effect of sales promotion on the interest in visiting de Karanganjar tourists in Blitar Regency, to analyze the effect of information quality on visiting intentions of de Karanganjar tourists in Blitar Regency. The analysis carried out in this study was by using a component-based SEM method using PLS as an analytical tool. The results showed that sales promotion had a significant positive effect on the intention to visit Karanganjar. This shows that the more attractive the sales promotion is carried out and can be reached by all consumers, the more it encourages consumers to visit to travel and buy coffee products at de Karanganjar. The quality of information has a significant (positive) effect on the interest in visiting the Karanganjar Koffieplantage. This shows that the more interesting the quality of the information that is done and can be reached by all consumers, the more it encourages consumers to visit De Karanganjar to travel and buy coffee products.